Zircon U-Pb and Hf isotope constraints from the Ailao Shan-Red River shear zone on the tectonic and crustal evolution of southwestern China - Lin, T; Chung, S; Chiu, H; Wu, F; Yeh, M; Searle, M; Iizuka, Y (2012)
The Ailao Shan-Red River (ASRR) shear zone, one of the most prominent geologic strike-slip shear zones in Southeast Asia, consists of high-grade metamorphic complexes that provide a rare opportunity to sample the mid-crustal rocks along the western margin of the Yangtze Block of South China. Here we report combined, in-situ analyses of zircon U-Pb and Lu-Hf isotopes of eight gneisses from the Diancang Shan and Ailao Shan segments of the ASRR shear zone. Our zircon U-Pb data indicate that the rocks contain abundant magmatic zircons ranging in age from 1785 to 25Ma, with peak ages at ca. 770, 350 and 240Ma, suggesting three major periods of protolith formation. The 350-Ma zircons, observed only in an orthogneiss from the Diancang Shan, show uniform initial Hf isotopic ratios marked by high and positive ε Hf(T) values from +16 to +10. This is in contrast with the other two zircon populations that are more common, occurring in both the Diancang Shan and Ailao Shan, and overall delineate very heterogeneous Hf isotopic compositions, with ε Hf(T) values ranging from +15 to -16. Many zircons reveal distinctive core-rim age variations. Zircon rims, formed between ca. 34 and 26Ma, show significant variations in Th/U ratios (5-0.01) and ε Hf(T) values (+14 to -10) that suggest complicated magmatic and metamorphic zircon overgrowth during the Oligocene. The presence of both metamorphic and magmatic overgrowths on zircons suggests that the metamorphism reached upper amphibolite facies, corresponding to mid-crustal level P-T conditions, as also suggested by structural and petrologic data. Our data furthermore suggest that the ASRR gneisses were not produced solely by shear heating during the Tertiary strike-slip faulting, but are uplifted, mid-crustal basement rocks that formed essentially during two major stages of magmatism, represented by the Neoproterozoic Kangding Complex and Late Permian Emeishan large igneous province. As a result of the India-Asia collision, these basement rocks underwent regional magmatic and metamorphic overprinting in the Oligocene that, based on our relevant work (Searle et al., 2010, Geosphere, 6, 1-23), predated the initial left-lateral movement along the ASRR shear zone. The 350-Ma protolith, which requires a dominant depleted-mantle input in the petrogenesis, cannot be linked to any major magmatic events in South China but may be interpreted as part of the Paleotethys remnants that were later incorporated into the ASRR shear zone. © 2011 Elsevier B.V.